1991
DOI: 10.1111/j.1471-4159.1991.tb03441.x
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Catecholamines from Individual Adrenal Medullary Chromaffin Cells

Abstract: Catecholamine secretion has been measured with electrochemical techniques from isolated, single adrenal medullary chromaffin cells with carbon-fiber microelectrodes. The electrode tip, which is of similar dimensions to the cell, is placed adjacent to the cell to enable the measurement of local secretion. Secretion is caused by exposing the cell to nanoliter volumes of solution containing nicotinic receptor agonists or depolarizing agents. The identification of secreted substances is made with cyclic voltammetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
120
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(126 citation statements)
references
References 45 publications
5
120
0
Order By: Relevance
“…IGF-II also The spikes elicited are of similar size and time course for the two stimulation protocols. This is expected for an exocytosis measurement because the amount released per vesicle and the amount detected in a spike will be independent of the method used to initiate exocytosis (30,31). In both cases, the spikes are superimposed over a broad envelope, although the envelope is more obvious with IGF-II stimulation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…IGF-II also The spikes elicited are of similar size and time course for the two stimulation protocols. This is expected for an exocytosis measurement because the amount released per vesicle and the amount detected in a spike will be independent of the method used to initiate exocytosis (30,31). In both cases, the spikes are superimposed over a broad envelope, although the envelope is more obvious with IGF-II stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…In both cases, the spikes are superimposed over a broad envelope, although the envelope is more obvious with IGF-II stimulation. The envelope is partially due to overlapping of many spikes occurring simultaneously (30,31) and partially due to a background change associated with the IGF-II stimulation. The bottom trace shows the background shift induced by IGF-II addition and recorded in a ␤ cell not responding to the agonist.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, previous work using single-cell carbon fiber amperometry [30,31] has indicated that quantal size positively depends on cell Ca 2+ levels [32] by transitioning from Ω-form fusion transients to 'full collapse' events, thus expelling all granule contents [3,8,9]. We measured the quantal size of catecholamine secretion in Dyn transfected cells compared to untransfected controls to determine the relative occurrence of Ω-form 'kiss an run' to 'full collapse'.…”
Section: A Role For Dynamin I In High Frequency-evoked Exocytosismentioning
confidence: 99%
“…Adrenomedullary chromaffin cells secrete catecholamines in response to nicotinic cholinergic agonists [1][2][3]. Following activation of the nicotinic receptor, a non-selective cation channel, associated to the receptor, opens [4,5], and the membrane of chromaffin cells is depolarized [6][7][8].…”
Section: Introductionmentioning
confidence: 99%